Empirical methods for networks data: Social effects, network formation and measurement error - Arun Advani; Bansi Malde (Institute for Fiscal Studies (IFS), 2014)
In many contexts we may be interested in understanding whether direct connections between agents, such as declared friendships in a classroom or family links in a rural village, affect their outcomes. In this paper we review the literature studying econometric methods for the analysis of social networks. We begin by providing a common framework for models of social effects, a class that includes the 'linear-in-means' local average model, the local aggregate model, and models where network statistics affect outcomes. We discuss identification of these models using both observational and experimental/quasi-experimental data. We then discuss models of network formation, drawing on a range of literatures to cover purely predictive models, reduced form models, and structural models, including those with a strategic element. Finally we discuss how one might collect data on networks, and the measurement error issues caused by sampling of networks, as well as measurement error more broadly.
Keywords: C31; C81; Z13; 330; Networks; Social Effects; Peer Effects; Econometrics; Endogeneity; Measurement Error; Sampling Design